Angganada: Sebuah Komposisi Karawitan Bali - I Putu Angga Mahendra; Hendra Santosa; Ni Putu Hartini (Universitas Negeri Surabaya, 2022)
Angganada's composition aims to realize an idea or imagination about the anatomy of the human body as a motivation to encourage the achievement of an innovative piece of music. The method of creating works of art will be carried out in four stages, namely: the exploration stage, the second stage of experimentation, and the third stage of formation and ending with a performance. This form of composition still uses the grip and structure found in Balinese musical instruments in general, namely the Tri Angga. Tri Angga are the three main parts which are often called kawitan, crew, thrusters, like the human body which consists of head, body and legs. The anatomy of the human body is divided into four main parts, namely the head, body, hands and feet. The purpose of this composition is the sound of the body or Body Cak and facial expressions that are able to strengthen the meaning of Anggaada in collaboration with Balinese gamelan to distinguish the standard of Tri Angga from the anatomy of the human body. The media revealed in this work consists of combining two types of gamelan, namely gamelan Smara Pagulingan, Gender Wayang and Body Cak by producing sounds produced by hitting certain body parts, such as applause, vocal sounds, and hitting certain body parts. collaborate on the sidelines of the song so as to support the stylist's concept.